Katherine Mansfield and World War One - Kimber, Gerri; Sousa Correa, Delia da; Martin, W. Todd (Katherine Mansfield studies, 2014)
"Like the reclamation of women's war writings that we have already seen in relation to Virginia Woolf and others, Mansfield's literary response to the key political event of her time is fundamental to our understanding of her developing writerly style. It is in her responses to the war that we find a 'political Mansfield', and the articles in this volume provide us with a greater appreciation of Mansfield in her socio-historical context. In offering new readings of Mansfield's explicit and implicit war stories, the contributions to this volume refine and extend our knowledge of particular stories and their genealogy. They illuminate the specific and more general influences of the war on Mansfield's evolving technique and, jointly, they reveal the importance of the war on her literary language, as well as for her own particular brand of modernism. This volume helps develop our ideas of what constitute war writings and, in so doing, expands the scope of Mansfield scholarship and the field of First World War studies."--Back cover